2020
DOI: 10.3389/fonc.2020.605349
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alterations in Metastatic Ovarian Cancer From Gastrointestinal Cancer

Abstract: Reports indicate that most metastatic ovarian cancer (MOC) originates from gastrointestinal cancer (GIC). Notably, GICs metastasize to the ovary frequently via 3 main routes including hematogenous spread, lymphogenous spread, and transcoelomic spread. Nonetheless, the mechanism of the progression remains unknown, and only a handful of literature exists on the molecular alteration implicated in MOC from GIC. This work collected existing evidence and literature on the vital molecules of the metastatic pathway an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Although previous in vitro studies have suggested dose-dependent effects of PAUF and anti-PAUF treatments on cell signaling activations (Park et al, 2011;Kim et al, 2013) and anti-tumor effects , respectively, it is necessary to explore dose-response of anti-PAUF against ovarian cancer in future studies. 2) A recent bioinformatic study suggests that the OVCAR-5 cancer cell line may be a metastatic ovarian cancer of upper gastrointestinal origin (Blayney et al, 2016), however, even if our findings may not best represent primary ovarian cancer, they remain highly relevant in ovarian cancer settings, because clinically, up to 20% ovarian cancers are originated from other organs (mainly from the gastrointestinal system) and show poorer prognosis (Chen et al, 2020). Whether cancers metastasized to ovary tend to express higher level of PAUF and thus benefit more from anti-PAUF treatment than primary ovarian cancer are indeed worth of further investigation.…”
Section: Frontiers Inmentioning
confidence: 86%
“…Although previous in vitro studies have suggested dose-dependent effects of PAUF and anti-PAUF treatments on cell signaling activations (Park et al, 2011;Kim et al, 2013) and anti-tumor effects , respectively, it is necessary to explore dose-response of anti-PAUF against ovarian cancer in future studies. 2) A recent bioinformatic study suggests that the OVCAR-5 cancer cell line may be a metastatic ovarian cancer of upper gastrointestinal origin (Blayney et al, 2016), however, even if our findings may not best represent primary ovarian cancer, they remain highly relevant in ovarian cancer settings, because clinically, up to 20% ovarian cancers are originated from other organs (mainly from the gastrointestinal system) and show poorer prognosis (Chen et al, 2020). Whether cancers metastasized to ovary tend to express higher level of PAUF and thus benefit more from anti-PAUF treatment than primary ovarian cancer are indeed worth of further investigation.…”
Section: Frontiers Inmentioning
confidence: 86%
“…After that, the most common metastatic sites are the omentum, the parietal and visceral peritoneum, as well adjacent organs via direct implantation [ 10 , 36 ]. The current scenario of intraperitoneal dissemination in OC includes tumor cell proliferation and epithelial-mesenchymal transition (EMT), the latter of which results in tumor cell migration, and, conversely, mesenchymal epithelial transition (MET), which forces the colonization of tumor cells with the formation of peritoneal implants [ 5 , 15 , 37 , 38 ].…”
Section: Peritoneal Metastasismentioning
confidence: 99%
“…54,55 In addition to decreased sexual function, development of osteoporosis, increased risk of cardiac events, and dementia may occur. [56][57][58] Furthermore, it has been reported that ovary removal in women below the age of 45 appears to have an increased mortality risk compared to those above this age. 57 Many negative consequences can, however, largely be prevented by the use of hormone replacement therapy (HRT), which is advised in these specific situations.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian involvement in these patients is estimated to be <1%. 55,56 The high proportion of OM within the young population stresses the need for increased awareness in the interpretation of a newly found ovarian mass on diagnostic imaging tests, especially in case of a previous history of colorectal cancer. 57 It is possible that an OM is initially misdiagnosed and surgery for a presumed primary ovarian malignancy is performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation